![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
b \(\Leftrightarrow x^3\left(x-2\right)+10x\left(x-2\right)=0\)
\(\Leftrightarrow x\left(x-2\right)=0\)
hay \(x\in\left\{0;2\right\}\)
c: \(\Leftrightarrow\left(2x-3-x-5\right)\left(2x-3+x+5\right)=0\)
=>(x-8)(3x+2)=0
=>x=8 hoặc x=-2/3
d: \(\Leftrightarrow x^2\left(x-1\right)-4\left(x-1\right)^2=0\)
\(\Leftrightarrow\left(x-1\right)\left(x^2-4x+4\right)=0\)
=>x=2 hoặc x=1
e: \(\Leftrightarrow x\left(x^2-11x+30\right)=0\)
=>x(x-5)(x-6)=0
hay \(x\in\left\{0;5;6\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
b: \(\Leftrightarrow x\left(x^3-2x^2+10x-20\right)=0\)
\(\Leftrightarrow x\left(x-2\right)=0\)
hay \(x\in\left\{0;2\right\}\)
c: \(\Leftrightarrow\left(2x-3-x-5\right)\left(2x-3+x+5\right)=0\)
=>(x-8)(3x+2)=0
hay \(x\in\left\{8;-\dfrac{2}{3}\right\}\)
d: \(\Leftrightarrow x^2\left(x-1\right)-4\left(x-1\right)^2=0\)
\(\Leftrightarrow\left(x-1\right)\left(x^2-4x+4\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x-2\right)^2=0\)
=>x=1 hoặc x=2
![](https://rs.olm.vn/images/avt/0.png?1311)
B1 : a, M = x3-3xy(x-y)-y3-x2+2xy-y2
= ( x3-y3)-3xy(x-y) -(x2-2xy+y2)
= (x-y)(x2+xy+y2)-3xy(x-y)-(x-y)2
= (x-y) [(x2+xy+y2-3xy-(x-y)]
= (x-y)[(x2-2xy+y2)-(x-y)
= (x-y)[(x-y)2-(x-y)]
= (x-y)(x-y)(x-y-1)
= (x-y)2(x-y-1)
= 72(7-1) = 49 . 6= 294
N = x2(x+1)-y2(y-1)+xy-3xy(x-y+1)-95
= x3+x2-(y3-y2)+xy-(3x2y-3xy2+3xy)-95
= x3+x2-y3+y2+xy-3x2y+3xy2-3xy-95
= (x3-y3)+(x2-2xy+y2)-(3x2y+y2)-(3x2y-3xy2)-95
=(x-y)(x2+xy+y2)+(x-y)2-3xy(x-y)-95
= (x-y)(x2+xy+y2+x-y-3xy)-95
= (x-y)[(x2-2xy+y2)+(x-y)]-95
= (x-y)[(x-y)2+(x-y)]-95
=(x-y)(x-y)(x-y+1)-95
= (x-y)2(x-y+1)-95
= 72(7+1)-95=297
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(9^{30}-27^{19}\right):3^{57}+\left(125^9-25^{12}\right):5^{24}\)
\(=\left(3^{60}-3^{57}\right):3^{57}+\left(5^{27}-5^{24}\right):5^{24}\)
\(=3^{57}\left(3^3-1\right):3^{57}+5^{24}\left(5^3-1\right):5^{24}\)
\(=3^3-1+5^3-1\)
\(=27-1+125-1\)
\(=150\)
2 )
\(x^2-25-\left(x+5\right)=0\)
\(\Leftrightarrow\left(x+5\right)\left(x-5\right)-\left(x+5\right)=0\)
\(\Leftrightarrow\left(x+5\right)\left(x-5-1\right)=0\)
\(\Leftrightarrow\left(x+5\right)\left(x-6\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x+5=0\\x-6=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-5\\x=6\end{matrix}\right.\)
Vậy ...
b )
\(\left(2x-1\right)^2-\left(4x^2-1\right)=0\)
\(\Leftrightarrow4x^2-4x+1-4x^2+1=0\)
\(\Leftrightarrow2-4x=0\)
\(\Leftrightarrow4x=2\)
\(\Leftrightarrow x=\dfrac{1}{2}\)
Vậy ...
c )
\(x^2\left(x^2+4\right)-x^2-4=0\)
\(\Leftrightarrow x^2\left(x^2+4\right)-\left(4+x^2\right)=0\)
\(\Leftrightarrow\left(x^2-1\right)\left(x^2+4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x^2-1=0\\x^2+4=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x^2=1\\x^2=-4\left(L\right)\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=-1\end{matrix}\right.\)
Vậy ...
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
\(A=x^2+4x-21-\left(2x^2-2x-5x+5\right)\)
\(=x^2+4x-21-2x^2+7x-5\)
\(=-x^2+11x-26\)
Khi x=0thì A=-26
Khi x=1 thì \(A=-1+11-26=10-26=-16\)
Khi x=-1 thì \(A=-1-11-26=-38\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) x3 - 3x2 = 0
<=> x2( x - 3 ) = 0
<=> \(\orbr{\begin{cases}x^2=0\\x-3=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=3\end{cases}}\)
2) 5x( x - 2020 ) - x + 2020 = 0
<=> 5x( x - 2020 ) - ( x - 2020 ) = 0
<=> ( x - 2020 )( 5x - 1 ) = 0
<=> \(\orbr{\begin{cases}x-2020=0\\5x-1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2020\\x=\frac{1}{5}\end{cases}}\)
3) ( 3x - 5 )2 = ( x + 1 )2
<=> ( 3x - 5 )2 - ( x + 1 )2 = 0
<=> [ ( 3x - 5 ) - ( x + 1 ) ][ ( 3x - 5 ) + ( x + 1 ) ] = 0
<=> ( 3x - 5 - x - 1 )( 3x - 5 + x + 1 ) = 0
<=> ( 2x - 6 )( 4x - 4 ) = 0
<=> \(\orbr{\begin{cases}2x-6=0\\4x-4=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=3\\x=1\end{cases}}\)
4) ( x2 - 2x )2 - 2( x - 1 )2 + 2 = 0
<=> ( x2 - 2x )2 - 2( x2 - 2x + 1 ) + 2 = 0
<=> ( x2 - 2x )2 - 2x2 + 4x - 2 + 2 = 0
<=> ( x2 - 2x )2 - 2( x2 - 2x ) = 0
<=> ( x2 - 2x )( x2 - 2x - 2 ) = 0
<=> \(\orbr{\begin{cases}x^2-2x=0\\x^2-2x-2=0\end{cases}}\)
+) x2 - 2x = 0 <=> x( x - 1 ) = 0 <=> \(\orbr{\begin{cases}x=0\\x-1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
+) x2 - 2x - 2 = 0
<=> x2 - 2x + 1 - 3 = 0
<=> ( x2 - 2x + 1 ) = 3
<=> ( x - 1 )2 = ( ±√3 )2
<=> \(\orbr{\begin{cases}x-1=\sqrt{3}\\x-1=-\sqrt{3}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=1+\sqrt{3}\\x=1-\sqrt{3}\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
A = (x - 2)(x2 + 2x + 4) - x(x - 2)(x + 2) - 2(2x + 1)
= x(x2 + 2x + 4) - 2(x2 + 2x + 4) - x(x2 - 4) - 2(2x + 1)
= x3 + 2x2 + 4x - 2x2 - 4x - 8 - x3 + 4x - 4x - 2
= (x3 - x3) + (2x2 - 2x2) + (4x - 4x + 4x - 4x) + (-8 - 2) = -10 => không phụ thuộc vào x
B = (x + 1)3 - x(x - 2)2 - 7(x2 + 1) - (1 - x) + 2
= x3 + 3x2 + 3x + 1 - x(x - 2)(x - 2) - 7x2 - 7 - 1 + x + 2
= x3 + 3x2 + 3x + 1 - x(x2 - 4x + 4) - 7x2 - 7 - 1 + x + 2
= x3 + 3x2 + 3x + 1 - x3 + 4x2 - 4x - 7x2 - 7 - 1 + x + 2 = (x3 - x3) + (3x2 + 4x2 - 7x2) + (3x - 4x + x) + (1 - 7 - 1 + 2) = - 5 => không phụ thuộc vào x